E-Restaurant - Wan Azmi, Wan Nur Syazrah (Universiti Teknologi Petronas, 2006)
Food & Beverage Dine-in Ordering System is actually to transform the labor-intensive way of taking an order in restaurants in Malaysia to a computerized system. The objectives of the system are to minimize the number of employee and the cost of labor. As well ofminimizing the cost and employee, it will also help to avoid probable to make mistake since it is a machine and it will be done by the customers itself. As technology changes, everything in Malaysia have been changed according to the latest technology but not for the ordering system. The methodology that will be use throughout the project is Rapid Application Development (RAD) method. There are 4 phases in using RAD method which are; Requirement Planning, User Design, Construction and Cut Over. The final phase will be implementing after the system has been finish.